Penyesuaian Budaya dalam Perkawinan - Hidayati, Sri (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2017)
The meaning of marriage is not just a meeting of two individuals, but also a cultural encounter behind both. To achieve success marital couples should make the process of cultural adjustment. This study aimed to describe the profile of cultural adjustment in the marital from aspects of thoughts, feelings, and actions of the husband or wife to her lover. The method used is descriptive method with quantitative approach. These samples included 50 people. Data were collected using a questionnaire designed based on the ordinal scale. Data analysis using Pearson Product Moment correlation. The results showed cultural adjustment in marriage at all respondents have achieved well adjustment. This conclusion is supported by data that measured three aspects of the figure level adjustment respondents as follows: 61 percent thought aspect, the aspect of feeling 84 percent, and 71 percent of the action aspects.